2020
DOI: 10.1128/aac.01783-19
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series and Literature Review of Isavuconazole Use in Pediatric Patients with Hemato-oncologic Diseases and Hematopoietic Stem Cell Transplantation

Abstract: We analyzed the use of isavuconazole (ISA) as treatment or prophylaxis for invasive fungal disease (IFD) in children with hemato-oncologic diseases. A multicentric retrospective analysis was performed among centers belonging to the Italian Association for Pediatric Hematology and Oncology (AIEOP). Pharmacokinetic (PK) monitoring was applied by a high-performance liquid chromatography-tandem mass spectrometry (HLPC-MS/MS) assay. Twenty-nine patients were studied: 10 during chemotherapy and 19 after allogeneic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 26 publications
8
36
1
Order By: Relevance
“…The clinical phase III trial SECURE found the majority of s-ISZ measurements were within the range of 1–7 mg/L [ 23 ]. The median value in the present study was 4.3 mg/L and well within that range, the same as in other studies [ 7 , 8 , 9 , 12 , 17 , 24 , 25 , 26 ]. In the present study, the majority of the s-ISZ measurements were also within the recommended range, but for VRZ a third of TDM measurements were outside the recommended range, which is also in accordance with the literature [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The clinical phase III trial SECURE found the majority of s-ISZ measurements were within the range of 1–7 mg/L [ 23 ]. The median value in the present study was 4.3 mg/L and well within that range, the same as in other studies [ 7 , 8 , 9 , 12 , 17 , 24 , 25 , 26 ]. In the present study, the majority of the s-ISZ measurements were also within the recommended range, but for VRZ a third of TDM measurements were outside the recommended range, which is also in accordance with the literature [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Adverse events to ISZ in the present study were mostly gastroenteric and hepatic, reported by the treating physician and also reported by others [ 12 , 14 , 25 , 29 , 30 , 31 ]. Adverse events were not closely related to high median TDMs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…and mucorales) reported on an excellent overall survival of 80.6% on day 42 [76]. Although a retrospective study including 29 immunocompromised children receiving isavuconazole off-label suggested the usefulness of the compound in the pediatric setting, data of isavuconazole in children are very limited [77]. As there is a lack of pediatric data regarding the treatment of rare molds, such as Fusarium spp.…”
Section: Treatment Recommendationsmentioning
confidence: 99%